Strategi Komunikasi Rumah Halal Nusantara dalam Pendampingan Proses Produk Halal (PPH) Bagi Usaha Mikro Kecil di Kota Depok - Yulianto; Marhanani Tri Astuti; Amun (EduInovasi: Journal of Basic Educational Studies, 2024)
The growth of the Muslim population in Indonesia has driven the expansion of the halal industry, creating opportunities for halal product services. This study examines the communication strategies implemented by Rumah Halal Nusantara. Using a descriptive qualitative approach, the study shows that effective communication by Halal Product Process (PPH) facilitators is crucial in simplifying the halal certification process for Micro and Small Enterprises. The use of WhatsApp as a communication tool is highly beneficial in providing quick and interactive support. This study highlights the importance of well-structured communication strategies in ensuring the success of the halal certification program. The use of digital platforms like WhatsApp enables real-time communication, making the process more accessible for business owners. Rumah Halal Nusantara's communication strategy in assisting Micro and Small Enterprises to obtain halal certification in Depok City can serve as a model of facilitation. This study emphasizes the importance of continuous support and education to ensure the successful implementation of the halal certification program, ultimately contributing to the growth of the halal industry in Indonesia.